Moxibustion-mediated alleviation of synovitis in rats with rheumatoid arthritis through the regulation of NLRP3 inflammasome by modulating neutrophil extracellular traps - Miao Wang; Hongfang Zhao; Hui Zhao; Chenlu Huo; Yu Yuan; Yan Zhu (Heliyon, 2024)
Purpose: This study investigates the potential mechanism of moxibustion in the treatment of rheumatoid arthritis (RA) by regulating the neutrophil extracellular trap (NET)/NOD-like receptor family pyrin domain-containing protein 3 (NLRP3) inflammasome axis with the use of a rat model with adjuvant arthritis (AA). Methods: Four groups, including normal control (NC), AA, moxibustion (MOX), and chlor-amidine (Cl-amidine) were created from 24 Wistar male rats (6 rats/group). After the intervention and treatment respectively, the joint swelling degree (JSD) and arthritis index (AI) were compared. The pathological changes of synovium were observed with hematoxylin and eosin staining and transmission electron microscopy. The formation of NETs in synovial tissues was detected with immunofluorescence staining. The protein expression of myeloperoxidase (MPO), neutrophil elastase (NE), citrullinated histone (Cit-H3), acyl arginine deiminase 4 (PAD-4), and NLRP3 was measured in the synovium of rat ankle joints with western blotting, and the levels of anti-cyclic citrullinated peptide antibody (CCP-Ab) and interleukin (IL)-1β were examined in rat serum with ELISA. Results: AA modeling markedly increased JSD, AI, synovial protein expression of MPO, NE, Cit-H3, PAD-4, and NLRP3, and serum levels of CCP-Ab and IL-1β in rats (P < 0.01). JSD and AI, as well as the levels of MPO, NE, Cit-H3, PAD-4, NLRP3, CCP-Ab, and IL-1β, were significantly lowered in AA rats by MOX and Cl-amidine (P < 0.01). In addition, AA modeling caused severe pathological injury in the synovium of rats, which was annulled by MOX and Cl-amidine. The formation of NETs in synovium was substantially promoted in rats by AA modeling and was significantly reduced in AA rats after the treatment. Conclusion: Moxibustion can markedly alleviate synovitis and repress inflammatory factor release in AA rats, which may be achieved by diminished synthesis of NETs or their constituents and the blocked formation of NLRP3 inflammasome.